Uso de equipamentos estéreos pessoais em jovens nas cidades de São Luís e São Paulo - Rodrigues, Alice Sampaio (2009)
Introduction: The increasing exposure to high sound pressure levels of personal listening devices (PLD), better known as MP3 players and iPods, reach sound intensities ranging from 60 to 125 dB (A), and has been raising concern on health professionals. Users of PLD have the habit of increasing the volume control to hide the background sounds such as a conversation, traffic or environmental noises. If used in an inappropriate way, these devices can cause risk of hearing impairment. Purpose: To characterize the use of personal listening devices in youths living in the cities of São Luis and São Paulo, considering if the sex and geographical area as sources of variability. Method: The sample comprised 80 university students, aged between 18 and 30 years old, living in the cities São Luis and São Paulo, equally divided by sex. The procedure consisted of applying a questionnaire containing 12 objective questions. Results: For the 80 students, it was found as sound habits the following: listening to the PLD for "more than three years" for 32 (80.0%) of youngsters from São Paulo and 14 (35.0%) from São Luis; concerning to the use of the devices "for more than two hours" a day, 14 (35.0%) youngsters in São Paulo and 20 (50.0%) in São Luis; the most frequent position of the volume control was "half" for 28 (70.0%) in São Paulo, and 22 (55.0%) in São Luis; the most frequent type of phone was insertion for 39 (97.5%) subjects in the two cities, and for the request made to users of PLD to lower the volume, four (20.0%) of female users and 13 (65.0%) males in São Luis were asked to lower it. In São Paulo, there were no differences among the samples, six (30.0%) for both genders. The majority the interviewed (40 (100.0%) in São Luis and 37 (92.5%) in São Paulo) answered that to use the PLD in maximum volume can cause hearing impairment. Conclusion: The results revealed statistically significant differences among youngster s sound habits in the two cities, revealing that sex and geographical region are sources of variability